Routing alogrithm over semi-regular tessellations - Kumarave, A.; Rangarajan, K. (2013 IEEE Conference on Information and Communication Technologies, 2013)
Path discovery or routing algorithms are challenging when the nodes are distributed over not on just regular grid like rectangular type but on semiregular grids. Investigations in the study of finite state automata that move about in a two dimensional space are suitable to tackle this context. The model proposed by H. Muller [1] is used here to construct new automaton which can explore the path through obstacles over the grid. This model is to be applied for routing phase for data transmission. The earlier results were shown for static obstacles distributed over integer grid and the automaton in this case was constructed to interact on the rectangular grid location endowed with four neighborhood directional states. In this paper we allow higher degree of neighborhood and mixing the types cells. It has been verified that the finite automaton with number of printing (output) symbols determined by the maximum out degree of a cell in the underlying semi-regular grid can find the target.